Social Illness Before and After the COVID-19 Pandemic: A Regional Study. Issue 2 (13th April 2023) - Stirparo, Giuseppe; Pireddu, Roberta; Andreassi, Aida; Sechi, Giuseppe Maria; Signorelli, Carlo
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) has dramatically changed the epidemiology of several diseases. Much evidence on this has been published in the pandemic phase. In addition, many studies have shown that phenomena such as stress, substance abuse, and burnout increased in the general population during the lockdown. Unfortunately, few studies analyze the post-pandemic phase. Study Objective: The study aimed to evaluate the trend of broad social problems, such as a diagnosis by the emergency department (ED), in the post-pandemic phase in the Lombardy (Italy) region. Methods: The study is a retrospective observational cohort study. All admissions to emergency rooms in the Lombardy region registered in the Emergency Urgency OnLine (EUOL) portal made from January through June 2019 were analyzed, having as main causes: psychiatric disorders, self-harm, substance abuse, social disadvantage, and violence. All accesses in emergency rooms in the Lombardy region registered in the EUOL portal made from January 1, 2019 through June 30, 2019 were analyzed and compared with the same period in 2022. Results: The study recorded an increase in the likelihood of events of self-harm (OR = 2.1; 95% CI, 1.8-2.6; P <.0001), substance abuse (OR = 1.2; 95% CI, 1.1-1.3; P <.0001), violence by others (OR = 1.3; 95% CI, 1.2-1.4; P <.0001), and social disadvantage (OR = 1.2; 95% CI, 1.1-1.4; P = .0045). The events are more concentrated in suburban areas (OR = 1.3; 95% CI, 1.2-1.4; P <.001). Conclusion: The increase in diagnoses of these social problems in the ED is only the culmination of a phenomenon that hides an underlying rise in social illness. In the post-COVID-19 phase, there is a need to invest in community care and social illness prevention policies.